Bibliometric Analysis of Herbal Therapy Interventions for Postpartum Depression in Maternal Health - Wulan Anugrah Pauji Salam; Rosidah Solihah; Aulia Ridla Fauzi; Sandriani; Elis Noviati (Pharmacogenius Journal, 2026)
Background: Postpartum depression (PPD) is one of the most common maternal mental health disorders, affecting mothers' well-being, maternal–infant bonding, and child development. Although pharmacological treatment remains the standard approach, concerns regarding medication safety during breastfeeding have increased interest in herbal therapy as a complementary or alternative intervention. Scientific publications on herbal therapy for PPD have grown substantially; however, the global research landscape has not been comprehensively mapped. Objective: This study aimed to analyze global research trends, publication characteristics, collaboration networks, influential authors, institutions, countries, journals, and emerging research themes related to herbal therapy interventions for postpartum depression in maternal health using bibliometric analysis. Methods: A bibliometric study was conducted using publications retrieved from the Scopus database. Relevant documents published between [insert study period, e.g., 2000–2025] were identified using predefined search keywords related to postpartum depression, herbal therapy, and maternal health. Bibliometric indicators, including annual publication trends, country and institutional productivity, authorship, citation analysis, journal performance, keyword co-occurrence, co-authorship, and thematic evolution, were analyzed using Biblioshiny (RStudio) Results: The bibliometric analysis demonstrated a continuous increase in scientific publications on herbal therapy for postpartum depression over the study period. Research productivity was concentrated in several high-income countries, with strong international collaborations among leading institutions. Frequently occurring keywords included postpartum depression, herbal medicine, Chinese herbal medicine, maternal health, complementary therapy, and mental health, indicating a growing research focus on integrative approaches for maternal mental health. Citation analysis identified several highly influential publications that have shaped the development of this research field, while network visualization revealed emerging themes involving complementary medicine, breastfeeding, anxiety, and maternal well-being. Conclusion: Research on herbal therapy interventions for postpartum depression has shown significant global growth and increasing scientific interest. Bibliometric mapping provides valuable insights into the intellectual structure, research hotspots, and collaboration patterns in this field. The findings may serve as a reference for researchers, clinicians, and policymakers in developing evidence-based complementary interventions and identifying future research priorities in maternal mental health.